Panel M.T.C. Building system for rural houses in the region of Boyacá, Colombia (REVISTA NODO, 2019)
This paper describes the process and outcomes of “Panel M.T.C” research as an innovative building system for rural houses in Boyacá (Colombia). Housing in this context is an important issue as it involves remote areas, characterized by extreme poverty. Nowadays, traditional building techniques have been supplanted by more modern solutions although they are hardly applicable in rural areas and unaffordable because they involve imported materials. The proposal of Panel M.T.C. is based on the reinterpretation of bahareque2 , using local resources (wood, earth, caña brava) and recovering ancestral knowledge related to the local tradition. The research is divided into two parts, one on the socio-cultural context and the other on building techniques. For this purpose, a workshop with artisans was launched in Ráquira (municipality of Boyacá) and some local inhabitants have been interviewed. The panel is modular in order to facilitate prefabrication while the completion occurs by self-construction. This solution achieves flexible one storey housing, where sustainability is key to respond environmental, social and economic needs. Eventually, this project could be applied in comparable contexts of the world with few changes to fit local conditions.
Keywords: Colombian rural architecture; Buildings in cob and caña brava; Sustainability; Tacit knowledge; cultural identity; Participatory design